CALCULATION OF POWER REQUIREMENTS TO DRIVE THE BELT WINDER PROTOTYPE PRINTED BY A 3D PRINTER - Danang Murdiyanto; Bernardus Crisanto Putra Mbulu; Iga Yuswantoro (Mechanical, Energy and Material (METAL), 2023)
The industrial world in the field of medium and large scale construction and maintenance from both various industrial sectors needs to improve procedures with technology that is efficient, safe, can reduce costs, and can minimize process time. Based on the experience of researchers in the agricultural machinery industry when installing and replacing belts on conveyors is done manually, namely by moving the belt using a forklift and according to researchers it is less efficient. The design of this prototype belt winder is to present the actual performance mechanism of the belt winder machine. The method used is to calculate the prototype design, design using 3d software, then the model is printed using a 3d printer. The last process carried out by researchers is assembling each component, then conducting trials and observing the performance mechanism of the prototype belt winder. The results obtained are able to roll a 1030 mm long belt with the required motor power of 5.31 Watt.